2016
DOI: 10.3892/ijo.2016.3716
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long non-coding RNA-associated ceRNA network reveals potential lncRNA biomarkers in human lung adenocarcinoma

Abstract: Accumulating evidence has highlighted the important roles of long non-coding RNAs (lncRNAs) acting as competing endogenous RNAs (ceRNAs) in tumor biology. However, the roles of cancer specific lncRNAs in lncRNA-related ceRNA network of lung adenocarcinoma (LUAD) are still unclear. In the present study, the 465 RNA sequencing profiles in LUAD patients were obtained from the cancer genome atlas (TCGA) database, which provides large sample RNA sequencing data free of charge, and 41 cancer specific lncRNAs, 25 miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 67 publications
3
106
0
Order By: Relevance
“…4 Study of molecular biomarkers and genetic abnormalities of lung adenocarcinoma will provide a new theoretical approach to diagnosis and clinical strategies. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…4 Study of molecular biomarkers and genetic abnormalities of lung adenocarcinoma will provide a new theoretical approach to diagnosis and clinical strategies. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…It presented a hypothesis about how ceRNAs regulated other RNA transcripts by competing for miRNAs. It could be seen that ceRNA network has been built in many cancer types, such as colorectal cancer and lung cancer . These results indicate that lncRNAs prove to be significant in tumorigenesis.…”
Section: Discussionmentioning
confidence: 86%
“…With the development of high-throughput technologies and the improvement of various databases [14,[48][49][50][51][52][53], some studies have demonstrated that the molecular biological characteristics of left-and right-sided colon cancers impact prognosis. Chromosomal instability (CIN) is one of the manifestations that may cause inactivation of the tumor suppressor gene p53 and is considered an independent prognostic factor for colon cancer [54].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%